2014
DOI: 10.1007/s00259-014-2899-z
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of 11C-ORM-13070 in PET imaging of α2C-adrenoceptors in vivo in the human brain

Abstract: The results of this study support the use of [(11)C]ORM-13070 PET in the quantitative assessment of α2C-adrenoceptors in the human brain in vivo. Reliable assessment of specific tracer binding in the dorsal striatum is possible with the help of reference tissue ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 24 publications
5
33
0
Order By: Relevance
“…PET imaging was performed with an HRRT (High Resolution Research Tomograph, Siemens, Knoxville, TN) brain scanner, with 207 slices of 1.22 mm covering the whole brain (axial FOV 25.3 cm) in the same manner as described by Lehto et al (). Image reconstruction was performed with the OP‐OSEM algorithm (Hong et al ) with eight iterations and 16 subsets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PET imaging was performed with an HRRT (High Resolution Research Tomograph, Siemens, Knoxville, TN) brain scanner, with 207 slices of 1.22 mm covering the whole brain (axial FOV 25.3 cm) in the same manner as described by Lehto et al (). Image reconstruction was performed with the OP‐OSEM algorithm (Hong et al ) with eight iterations and 16 subsets.…”
Section: Methodsmentioning
confidence: 99%
“…These studies revealed that [ 11 C]ORM‐13070 penetrated rapidly into the brain with the most prominent accumulation of radioactivity occurring in the caudate nucleus and putamen. The test–retest reliability of the uptake was good, with absolute variability of 4.3% in the putamen and 6.5% in the caudate nucleus (Lehto et al, ; Luoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is debatable whether VAS is a sensitive enough method to assess the sedative effects of anesthetic agents, and the ROI-based analysis did suggest that high-dose dexmedetomidine had a global effect on thalamic tracer binding, while the low dose had no or negligible effects, less than the thalamic test-retest variability of [ 11 C]ORM-13070 binding (see below). The small sample size (n 5 6) restricts the interpretation of the current results even though thalamic [ 11 C]ORM-13070 binding has been previously shown to be highly repeatable with an absolute variability of 6.6% (Lehto et al, 2015a). The relevance of the statistically significant isolated cortical finding is unclear with regard to previously published data on dexmedetomidine and the CNS effects of anesthetic agents in general.…”
Section: Discussionmentioning
confidence: 72%
“…The relevance of the statistically significant isolated cortical finding is unclear with regard to previously published data on dexmedetomidine and the CNS effects of anesthetic agents in general. It is also acknowledged that the cortical repeatability of [ 11 C]ORM-13070 binding is rather poor with an absolute test-retest variability of 13-14% (Lehto et al, 2015a). When PET tracer binding is estimated with tissue ratios following a bolus injection, decreased regional CBF could affect binding estimates by decreasing the efflux (k 2 ) from the free tissue compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation